Место молодежной субкультуры в культурном многообразии - Москаленко, Л.Б. (Культура народов Причерноморья, 2014)
В статье рассматривается место молодежной субкультуры, являющейся частью как
массовой, так и популярной культуры, анализируется взаимосвязь элитарного и популярного и
популярного культурных пластов с молодежной субкультурой. У статті розглядається місце молодіжної субкультури, яка є частиною як масової, так і
популярної культури, аналізується взаємозв'язок елітарного і популярного культурних пластів з
молодіжною субкультурою. The article discusses the location of the youth subculture, which is part of mass and popular culture,
explores the relationship of elite and popular cultural layers with youth subculture.Youth subculture tends to
innovations, creativity, emphasizing their own autonomy and independence. In youth environment the direction
to the creation of their own identity is strongly shown.
Attention is paid to the growing influence of media on youth subculture. The article describes the terms "moral
panic" and "media panic." The analysis of moral panic is aimed at establishing of deep contradictions between
the young and the older generation. It is noted that modern moral standards have changed their characteristics
under the influence of multiple means of communication. Youth cultural education is constantly updated,
becausе there are always searching in society.